K0.5Na0.5VO3-SiO2 Co-sintering Agent of Ceramic Mg0.8Ti0.2O3 as Dielectric Material Candidate - Sefrilita Risqi Adikaning Rani; Ika Widya Wahyuningsih; Cindi Regita Cahyani (Universitas Islam Negeri (UIN) Mataram, 2023)
This paper focuses on the characteristics of K0.5Na0.5VO3 (KNV) and SiO2 when added to Mg0.8Zn0.2TiO3 (MZT) material to reduce the sintering temperature. Initially, a single phase of Mg0.8Zn0.2TiO3 (MZT) was synthesized using the conventional solid-state reaction method at 850°C for 4 hours. Subsequently, (K0.5Na0.5)VO3 was formed as a single phase at a temperature of 500°C for 2 hours. The reduction of MZT sintering temperature was then carried out by adding K0.5Na0.5VO3 and SiO2 and sintering at 950°C for 4 hours. Adding K0.5Na0.5VO3 and SiO2 resulted in a maximum density value of 2.76 g/cc and an average grain size of 3 µm based on scanning electron microscopy (SEM) analysis. The optimal composition was found to be 0.7MZT-0.25KNV-0.05SiO2. X-ray diffraction (XRD) characterization using the Rietveld method revealed the presence of three phases: (Mg/Zn)TiO3, (K/Na)VO3, and MgTi2O5. Based on the results, it can be concluded that the (K/Na)VO3-SiO2 material can be effectively utilized as a sintering agent for (Mg/Zn)TiO3, reducing the sintering temperature of the material.